Creativity and identity. Participatory theater as a tool in the construction of reflective identity: the role of soft skills - Porankiewicz-Żukowska, Aleksandra (Creativity Studies, 2024)
In this article, I undertake an analysis of issues related to the role played by creativity in the process of identity construction, in particular reflective identity. As I see it, social changes characteristic of late modernity, mean that processes related to creativity and the development of emotional intelligence, have gained in importance in the context of identity development. Contemporary social reality also requires the stimulation of new competences useful for constructing reflective identity within the framework of nurturing and educational systems. Is it possible for participatory theater to act as a tool to support the development of creativity and thereby be employed in the development of reflective identity?